Expatriates in touch : a uses and gratifications study of Philippine online media among Filipinos in Singapore - Violeda Acosta Umali (2008)
This study was conducted with the general objective of describing what uses and gratifications the Philippine-based online media have for Filipinos based in Singapore. The research combined quantitative and qualitative methods - the survey and the ethnographic interview, respectively - to answer the following specific objectives: to describe the respondents' patterns of Philippine online media use, to determine what communication needs of the respondents are addressed by said media, to situate the respondents' use of the online media vis-a-vis other communication channels, to elucidate on the socio-psychological context of the respondents' online media use, and to present recommendations that would help make Philippine-based online media more responsive to the needs of its citizens abroad.